An Improved Image Steganography Scheme Based on RDWT and QR Decomposition - Ng, Ke-Huey; Liew, Siau-Chuin; Ernawan, Ferda (IOP Publishing, 2020)
This paper demonstrates an improved image steganography that hides grayscale secret image into grayscale cover image using RDWT and QR decomposition. The proposed scheme made use of the human visual system (HVS) in the embedding process. Both cover and secret image are being segmented into non-overlapping blocks with identical block size. Then, entropy values generated from every image block will be sorted from the lowest value to the highest value. The embedding process starts by embedding the secret image block with lowest entropy value into the cover image block with lowest entropy value. The process goes on until all image blocks have been embedded. Embedding secret image into cover image according to the entropy values causes differences that HVS can less likely to detect because of the small changes on image texture. The proposed scheme provides improvement in terms of imperceptibility, which gives higher values of PSNR and better image quality.